FIGURE 11 in New species of deepsea demosponges (Porifera) from the Aleutian Islands (Alaska, USA) - Lehnert, Helmut; Stone, Robert; Heimler, Wolfgang (Zenodo, 2006)
FIGURE 11. Euchelipluma elongata sp. nov. a, Fusiform choanosomal style. b, isochela and sigmas. c, Ectosomal tylostyle, slightly polytylote. d, Characteristic thin placochela. e, Developmental stage of polytylote tylostyle and two placochelae. f, Sigma. Published as part of Lehnert, Helmut, Stone, Robert & Heimler, Wolfgang, 2006, New species of deepsea demosponges (Porifera) from the Aleutian Islands (Alaska, USA), pp. 1-35 in Zootaxa 1250 on page 19, DOI: 10.5281/zenodo.173010